2017
DOI: 10.1002/2211-5463.12198
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of miR‐146a‐5p and its potential targets in hepatocellular carcinoma validated by a TCGA‐ and GEO‐based study

Abstract: Our previous research has demonstrated that miR‐146a‐5p is down‐regulated in hepatocellular carcinoma (HCC) and might play a tumor‐suppressive role. In this study, we sought to validate the decreased expression with a larger cohort and to explore potential molecular mechanisms. GEO and TCGA databases were used to gather miR‐146a‐5p expression data in HCC, which included 762 HCC and 454 noncancerous liver tissues. A meta‐analysis of the GEO‐based microarrays, TCGA‐based RNA‐seq data, and additional qRT‐PCR data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…miR-146a-5p functions as a tumor suppressor in various types of cancer, including hepatocellular carcinoma, esophageal squamous cell carcinoma, NSCLC and prostate cancer (20)(21)(22)(23). However, the role of miR-146a-5p in the development of TNBC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-146a-5p functions as a tumor suppressor in various types of cancer, including hepatocellular carcinoma, esophageal squamous cell carcinoma, NSCLC and prostate cancer (20)(21)(22)(23). However, the role of miR-146a-5p in the development of TNBC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (20) reported that miR-146a-5p was downregulated in hepatocellular carcinoma and acted as a tumor suppressor. Wang et al (21) revealed that miR-146a-5p promoted esophageal squamous cell carcinoma progression by regulating epithelial-mesenchymal transition (EMT) via targeting Notch2.…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al reported that miR-146a was significantly decreased in non-alcoholic steatohepatits (NASH) and that overexpression of miR-146a was capable of improving NASH by targeting HdMcP (27). In addition, miR-146a has been found to play an important role in liver cancer (28)(29)(30). However, there are few literature reports regarding whether miR-146a plays a role in the development of insulin resistance and NAFLd.…”
Section: Mir-146a Improves Hepatic Lipid and Glucose Metabolism By Tamentioning
confidence: 99%
“…Intracranial aneurysms [111], coronary heart disease [112], myocardial infarction [113], myocardial hypertrophy [114], dilated cardiomyopathy [115], pulmonary arterial hypertension [116], acute ischemic stroke [89], ascending aortic aneurysm [49] hsa-miR-145-5p 5q33 Hypertension [117,118], dilated cardiomyopathy [119], myocardial infarction [120,121], stroke [121], acute cerebral ischemic/reperfusion [122], T2DM [24,123], T1DM [52], diabetic retinopathy [124], gestational diabetes mellitus [125] hsa-miR-146a-5p 5q33.3 [126,127] Angiogenesis [128], hypoxia, ischemia/reperfusion-induced cardiac injury [129], myocardial infarction [17], coronary atherosclerosis, coronary heart disease in patients with subclinical hypothyroidism [130], acute ischemic stroke, acute cerebral ischemia [131], T2DM [24,52], T1DM [75], diabetic nephropathy [57] hsa-miR-181a-5p 1q32.1 9q33.3 [132] Regulation of hypertension-related genes [50], atherosclerosis [132], metabolic syndrome, coronary artery disease [133], non-alcoholic fatty liver disease [134], ischaemic stroke, transient ischaemic attack, acute myocardial infarction [135,136], obesity and insulin resistance [62,…”
Section: Introductionmentioning
confidence: 99%